Azriel Tan received Royal Academy Award (Medal of Excellence) - UMP, PNC (2019)
You only live once, live life to the fullest’ is the philosophy held by the recipient of Royal Academy Award (Medal of Excellence), Azriel Tan Zhe Khen, 24, the son of 54-year-old Tan Chong Phor, who works as an administrator and his mother Leong Wai Choy, 53, who is a housewife.